MANAJEMEN PANTI ASUHAN ATTAQWA MUHAMMADIYAH DALAM MEMBINA KEPRIBADIAN SISWA MTS MUHAMMADIYAH PADANG LUAR KECAMATAN RAMBATAN KABUPATEN TANAH DATAR - Armis Armis (IAIN Batusangkar, 2016)
This study was aimed at describing the management of reformatory of At-Taqwa Muhammadiyah on building the students’ personality MTs Muhammadiyah Padang Luar. The study was qualitative case study by applying interview, documentation and observation as instruments. The data were analyzed by using triangulation method. The results revealed that the buliding of students’ personality was done by internalizing the moral value both god’s interaction and human’s interaction such praying; memorizing quran, and social intercourse. The management of reformatory of At-Taqwa Muhammadiyah was done by planning the program; organizing the program; implementing the program and controlling the program Keywords: Management, Reformatory, Students’ Personality, MTs Muhammadiyah Padang Luar